Acute kidney injury: prevention, detection, and management. Summary of updated NICE guidance for adults receiving iodine-based contrast media. Issue 3 (March 2021) - Barrett, T.; Khwaja, A.; Carmona, C.; Martinez, Y.; Nicholas, H.; Rogers, G.; Wierzbicki, A.S.; Lewington, A.J.P.; Wierzbicki, Anthony S.; Allinson, Clare; Aylett, Virginia; et al.
Abstract : The National Institute for Health and Care Excellence (NICE) has recently updated the guideline for Acute kidney injury: prevention, detection and management (NG148), providing new recommendations on preventing acute kidney injury (AKI) in adults receiving intravenous iodine-based contrast media. The association between intravenous iodinated contrast media and AKI is controversial, particularly with widespread use of iso-osmolar agents. Associations between contrast media administration and AKI are largely based on observational studies, with inherent heterogeneity in patient populations, definitions applied, and timing of laboratory investigations. In an attempt to mitigate risk, kidney protection has typically been employed using intravenous volume expansion and/or oral acetylcysteine. Such interventions are in widespread use, despite lacking high-quality evidence of benefit. In the non-emergency setting, glomerular filtration rate (GFR) measurements should be obtained within the preceding 3 months before offering intravenous iodine-based contrast media. In the acute setting, adults should also have their risk of AKI assessed before offering intravenous iodine-based contrast media; however, this should not delay emergency imaging. Based on the evidence available from randomised controlled trials, the NICE committee recommends that oral hydration should be encouraged in adults at increased risk of AKI and that volume expansion with intravenous V fluids should only be considered for inpatients at particularly high risk.